A protective maternal nutrient concomitant intake associated with acute leukemia might be modified by sex, in children under 2 years - Mérida-Ortega, Ángel; Pérez-Saldivar, María Luisa; Espinoza-Hernández, Laura E.; Dorantes-Acosta, Elisa M.; Torres-Nava, José Refugio; Solís-Labastida, Karina A.; Paredes-Aguilera, Rogelio; Velázquez-Aviña, Martha M.; Espinosa-Elizondo, Rosa Martha; Miranda-Madrazo, M. Raquel; González-Ávila, Ana Itamar; Rodríguez-Villalobos, Luis Rodolfo; et al. (Frontiers in Oncology, 2023)
Maternal consumption during pregnancy has been inconclusively associated with acute leukemia (AL) in infants, probably since epidemiological evidence has emerged mainly from the analysis of one-by-one nutrient, which is incompatible with life. Our objective was to evaluate the association between AL in Mexican children under 2 years of age and their mothers’ nutrients concomitant intake during pregnancy, as well as to explore whether there are differences between girls and boys. We conducted a study of 110 cases of AL and 252 hospital-based controls in the Mexico City Metropolitan area from 2010 to 2019. We obtained information on maternal intake of 32 nutrients by a food frequency questionnaire and used weighted quantile sum regression to identified nutrient concomitant intakes. We found a concomitant intake of nutrients negatively associated with AL (OR 0.17; CI95% 0.03,0.88) only among girls; and we did not find a nutrient concomitant intake positively associated with AL. This is the first study that suggests nutrients that have been individually associated with AL are not necessarily the same in the presence of other nutrients (concomitant intake); as well as that maternal diet might reduce AL risk only in girls.